Evaluation of CO2 storage potential of Carboniferous sandstones in the Maritime Provinces of Canada - Carey, John S.; Durling, Paul (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2024)
The suitability of Carboniferous sandstones in three regions of the Maritime Provinces of Canada for geological carbon storage was evaluated: the Horton Bluff Formation in the Windsor Sub-basin, the lower Cumberland Group sandstones in the Cumberland–Sackville Sub-basin, and the Pennsylvanian sandstones of Prince Edward Island. The properties of potential reservoirs and characteristics of vertical seals and barriers to lateral migration were evaluated using previously collected well logs, sample descriptions, core analyzes and seismic interpretations. Reservoir quality was found to be the limiting factor in all three regions. Sandstones in the upper Hurd Creek Member of the Horton Bluff Formation locally have porosities up to 15% and permeabilities up to 25 milliDarcies at depths up to 1200 m. Their aggregate thickness may be suitable for GCS, but individual sandstones are thin and likely of limited lateral extent. The lower Cumberland Group contains sand-dominated successions up to 1 km thick with low porosity (5–7%) where known in the subsurface. Sandstone bodies in the Bradelle, Green Gables, and Cable Head formations beneath Prince Edward Island exceed tens of meters in thickness with porosities averaging up to 10–12% and permeabilities up to 10 milliDarcies. Evaporites in the overlying Windsor Group would provide a suitable seal for the Horton Bluff Formation; in other areas the top seal would be provided by mud-prone heterolithic intervals. The evaluated areas may provide opportunities for small onshore storage projects. Further work is warranted to delineate reservoir trends and verify the integrity of potential top seals and traps.